Lactose and specialty protein sources influence flow ability of nursery pig diets - Carney, E.E.; Groesbeck, C.N.; Goodband, Robert D.; Tokach, Michael D.; Nelssen, Jim L.; Dritz, Steven S. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2009)
Two experiments were conducted to determine the effects of lactose products and specialty protein sources on feed flow ability as measured by angle of repose. Angle of repose is the maximum angle in which a pile of ingredient retains its slope. A large angle of repose represents a steeper slope and poorer flow ability. A 70:30 corn-soybean meal blend served as the base to which all specialty ingredients were added. In Experiment 1, six lactose sources were evaluated. Three sources were fine, powdered whey permeates, and the other sources were coarse-ground whey permeate, edible-grade spray-dried whey, and a crystalline lactose source. Lactose sources were added at 0, 5, 10, 20, and 30% to the corn-soybean meal blend. Angle of repose was then measured on these mixtures, as well as on the individual lactose sources. There was a lactose source × level interaction (P<0.0001) observed. Increasing lactose source decreased angle of repose, but the coarse whey permeate had a much greater improvement in flow ability, resulting in the interaction. In Experiment 2, five specialty protein sources were evaluated: powdered or granulated spray-dried animal plasma, powdered or granulated spray-dried blood cells, and select menhaden fish meal. Specialty protein sources were added at 0, 2.5, 5, 7.5, and 10% to the 70:30 corn-soybean meal blend. There was a specialty protein source × level interaction (P<0.0001) observed. As powdered animal plasma and blood cells increased, angle of repose increased, resulting in poorer flow ability. With the addition of granulated animal plasma and blood cells, angle of repose decreased, indicating better flow ability. Increasing fish meal did not influence angle of repose. These data confirm that greater flow ability is observed with granulated specialty protein or coarsely ground lactose sources.
Swine research, 2005 is known as Swine day, 2005
Keywords: Angle of repose; Lactose; Flow ablility; Specialty protein sources; Swine